Body size predicts between-individual differences in exploration behaviour in the southern corroboree frog. (July 2017) - Kelleher, Shannon R.; Silla, Aimee J.; Dingemanse, Niels J.; Byrne, Phillip G.
Abstract : Proximate mechanisms underpinning between-individual variation in repeatedly expressed behaviours (animal personality) remain poorly understood. Recent theoretical models have focused on the concept of adaptive state-dependent behaviour, proposing that repeatable differences in behaviour emerge due to individual differences in repeatable state variables such as metabolic rate, age, sex or body size. Few studies have attempted to investigate the effect of state on personality empirically, and evidence for links between individual variation in state and personality remains equivocal. We used a captive colony of southern corroboree frogs, Pseudophryne corroboree, to (1) test for innate, temporally repeatable behavioural differences (animal personality) along the activity, exploration/avoidance and boldness/shyness behavioural axes, (2) test for behavioural syndromes (between-individual correlations between behavioural traits) and (3) determine whether behavioural traits are correlated with body size at the between-individual level. Individuals exhibited repeatable variation along all three behavioural axes, but between-individual correlations did not deviate from zero, providing no evidence for behavioural syndromes. Body size explained 40% of the between- individual variance in exploration behaviour, with larger frogs exhibiting greater mobility and travelling further in a novel environment. These associations indicate that there is potential for innate body size variation in P. corroboree to act as an important state variable underpinning repeatable between-individual behavioural differences. Future research may test this idea experimentally. Continued investigation of state-dependent individual behaviour in P. corroboree and other animals is likely to provide important insights into the proximate causes of animal personality. Highlights: We tested for animal personality signatures in captive southern corroboree frogs. Behaviour along the activity, exploration and boldness axes were quantified. Corroboree frogs exhibited personality along all three behavioural axes. Body size was a significant predictor of exploration personality. Our results imply that animal personality may be state dependent.